Suicide assistance in Germany: A protocol for a multi-perspective qualitative study to explore the current practice. - Sven Schwabe; Franziska A Herbst; Stephanie Stiel; Nils Schneider (PLoS ONE)
Background Suicide assistance is as a complex process comprising a series of stages, ranging from initial consultations with patients about end-of-life options to counselling bereaved family members. The role of healthcare professionals and other practitioners in this process varies according to national regulations and procedural requirements. After a decision of the German Federal Constitutional Court in 2020, suicide assistance is unregulated in Germany but official data about the implementation of suicide assistance is lacking. Aims The project "ASEP-Assisted suicide in Germany: Exploring the practice" aims to generate and disseminate scientific knowledge on the practice of assisted suicide in Germany, based on the experiences of practitioners and family members. Methods ASEP is a prospective, observational, qualitative study comprising three phases. In Phase 1, expert interviews will be conducted to identify involved professional groups, issues and stages of the implementation of suicide assistance in Germany. In phase 2, experiences of practitioners and family members, who were involved in the practice of suicide assistance in Germany, will be collected via semi-structured interviews and analysed. In phase 3, findings of phase 2 will be discussed in focus groups with experts to identify linkages between the practice of assisted suicide and the healthcare system and to develop recommendations on how these linkages should be organised. Discussion The results of this study will gain insights into the practice of suicide assistance for the first time in Germany. The findings are expected to inform scientific societies, professional association, and policy makers about the current practice and provide recommendations for better linkages of assisted suicide with the healthcare system. In this way, the project provides an evidence-based impetus for a more transparent and well-founded handling of assisted suicide in the German healthcare system. Trial registration The study was prospectively registered in the German Clinical Trials Register (Deutsches Register Klinischer Studien) (Registration N° DRKS00034574; date of registration: 04 July 2024). The study is searchable under the International Clinical Trials Registry Platform Search Portal of the World Health Organization, under the German Clinical Trials Register number.